LncRNA MEG3 inhibits self-renewal and invasion abilities of oral cancer stem cells by sponging miR-421 - Pei-Yin Chen; Pei-Ling Hsieh; Chih-Yu Peng; Yi-Wen Liao; Chuan-Hang Yu; Cheng-Chia Yu (Journal of the Formosan Medical Association, 2021)
Background/Purpose: Oral cancer stem cells (CSCs) have been considered as the key cells that are implicated in tumor recurrence and metastasis. In recent years, great attention has been paid to the significance of various non-coding RNAs due to their regulatory roles in oral CSCs. Although the function of long non-coding RNA MEG3 in various cancers has been investigated, its effects on the features of oral CSCs remained to be determined. Methods: The expression levels of MEG3 in tongue squamous cell carcinomas and prognostic effect have been evaluated. We assessed the expression of MEG3 in sphere cells (oral CSCs) using qRT-PCR. Secondary sphere formation and invasion assays were conducted to evaluate the self-renewal and metastatic abilities, respectively. Bioinformatics software and luciferase reporter assay were used to predict and verify the relationship between MEG3 and miR-421. Results: MEG3 was downregulated in the tissues of oral cancer and associated with a poor prognosis. In oral CSCs, the expression of MEG3 was repressed and overexpression of MEG3 resulted in suppression of self-renewal and invasion abilities. Luciferase reporter assay showed that miR-421 directly interacted with MEG3, and our subsequent experiment demonstrated that elevation of miR-421 reversed the MEG3-inhibited characteristics of oral CSCs. Conclusion: Our findings suggest that MEG3 can serve as a tumor suppressor in oral CSCs by impeding the action of miR-421. Moreover, targeting MEG3-miR-421 axis has the potential to mitigate the tumor recurrence and metastasis.